Terson’s Syndrome due to Ependymoma: A Rare Case Report: Poster Presentation - Case Report - Resident - Priscillia Tondolambung; Robby Tumewu (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Terson's syndrome is often associated with subarachnoid hemorrhage. Other reported causes, include trauma, tumors, hypertension, perioperative and postoperative intracranial hemorrhage, or increased intracranial pressure. This case demonstrates a unique pathogenesis of Terson's syndrome. Case Illustration : A 14-year-old boy presented with the blurred vision on both eyes 3 weeks ago, accompanied with nausea, vomiting, and headache, with normal blood pressure measurement (126/80mmHg). He also had a history of head injury. His visual acuity was 6/20 uncorrected with pinhole on both eyes. Both intraocular pressures within normal limits. The anterior segment showed bilateral mid-dilated reactive pupil. Funduscopy revealed bilateral papilledema with peripapillary hemorrhage, similar to retinal vein occlusion, which is suggestive with Terson’s Syndrome. Magnetic Resonance Imaging (MRI) scan showed an ependymoma mass. We consulted this case with Pediatric Neurosurgeon, who planned for ventriculoperitoneal shunt with craniotomy tumor removal. Discussion : Terson's syndrome now defined as any intraocular hemorrhage associated with intracranial hemorrhage or elevated intracranial pressures. In this case, the etiology was thought to be increased intracranial pressure, which may be caused by ependymoma. Ependymoma is one of the most common central nervous system tumors in children. Intraocular hemorrhage in Terson’s syndrome is often self-limiting, but ependymoma needs neurosurgical intervention, which has lower survival rates for children with posterior fossa tumors. Conclusion : There are still controversies regarding the pathogenesis of Terson's syndrome. Not the occlusion, but the compression of the central retinal vein, by the increased pressure of cerebrospinal fluid due to high intracranial pressure, which increases the retinal venous pressure and causes retinal hemorrhage.